Література факту на противагу масовій культурі - Колошук, Надія Георгіївна; Koloshuk, Nadiia H. (Інститут літератури ім. Т. Г. Шевченка НАН України, Бердянський державний педагогічний університет, 2007)
Речь идёт о комплексе документальных жанров в восточнославянских и польской литературах ХХ в., в частности о развитии «лагерного текста» о советских концлагерях (включая тексты-свидетельства непрофессиональных авторов), в контексте формирования постмодернистской культурной парадигмы с её мировоззренчески-эстетическим кризисом. Обоснованы взаимосвязи постмодернизма как направления с документальной литературой, которая функционирует и развивается на разных уровнях культуры – прежде всего как андеграундная в противодействии тиражированным в коммерческих целях белетристике и кичу. The article deals with an investigation is made into a range of nonfiction genres in twentieth-century eastern Slavic and Polish literature, and more specifically, into the development of “prison camp texts” about Soviet concentration camps along with firsthand accounts which were written by amateur authors within the context of the formation of the postmodern cultural paradigm with its crisis with respect to the aesthetic world outlook. Attention is given to the most important conflicts and problems related to debatable issues, to the poetic style of the prison camp texts and to the reception which they received. The interrelated streams within postmodernism are confirmed as representing a certain direction in nonfictional literature, which functioned and developed on different cultural levels, initially as underground publications in opposition to belles-lettres and kitsch publications that existed for commercial purposes.
Литература факта в противовес массовой литературе
Keywords: массовая литература; литература факта; лагерная проза; постмодернизм / постмодерн; лагерная проза; кич; belles-lettres; nonfiction; prison-camp prose; postmodernism / postmodern; non-fiction personal accounts; kitsch